FORENSIC DESCRIPTION OF SUITSID CASES - Hakimov Sarvar Abduazimovich; Salimova Malika Rashidbekovna; Gulyamov Dilshod Erkinovich (Western European Studies, 2024)
The choice of suicide method is influenced by the cultural environment, the presence of suicidal thoughts and intentions, easy access to suicide instruments, and similar factors. In addition, the gender paradox is also important, that is, parasuicidal cases are more often committed by women, while men often resort to lethal methods to end their suicidal intentions, such as the use of firearms, drowning, self-hanging - real is suicidal. Intentional self-poisoning is more typical of suicide attempts.
Keywords: Suicide; forensic examination